Thickness-dependence of block copolymer coarsening kinetics. Issue 18 (10th April 2017) - Black, Charles T.; Forrey, Christopher; Yager, Kevin G.
Abstract : The ordering kinetics of block copolymer thin films are influenced by film thickness. In particular, film edges act as sinks for defects, accelerating ordering kinetics. Abstract : Despite active research, many fundamental aspects of block copolymer ordering remain unresolved. We studied the thickness-dependence of block copolymer grain coarsening kinetics, and find that thinner films order more rapidly than thicker films. Bilayer films, or monolayers with partial layers of islands, order more slowly than monolayers because of the greater amount of material that must rearrange in a coordinated fashion. Sub-monolayer films order much more rapidly than monolayers, exhibiting considerably smaller activation energies, as well as larger exponents for the time-growth power-law. Using molecular dynamics simulations, we directly study the motion of defects in these film regimes. We attribute the enhanced grain growth in sub-monolayers to the film boundaries, where defects can be spontaneously eliminated. The boundaries thus act as efficient sinks for morphological defects, pointing towards methods for engineering rapid ordering of self-assembling thin films.